Effects of 5-Bromodeoxyuridine and 5-Iododeoxyuridine on a Latent Herpes Simplex Virus Infection - Varani, J. (1975)
A latent herpes simplex virus infection was established in rabbit kidney cells. Treatment of the cells with 5-bromo-2-deoxyuridine after the latent infection was established had no effect on the rate of virus recovery but did extend the latent period before active virus growth resumed. In contrast to this, treatment of cells with 5-bromo-2-deoxyuridine or 5-iodo-2-deoxyuridine prior to infection with virus increased the subsequent rate of virus recovery.